401 Three Birds with One Stone: Ureteric Calculus Precipitates Diagnosis and Resection of Three Primary Neoplasms. (4th May 2021) - Collins, P; O'Connell, C; Omer, S A; Inder, M S; Madden, A; Smyth, L; Casey, R; Manecksha, R; Thomas, A; Browne, R; O'Neill, A; Tierney, S; et al.
Abstract: A 67 year-old female presented to our centre with a 2 day history of right flank pain, clinically suggestive of ureteric colic. Computed tomography (CT) confirmed a 6mm right ureteric calculus. However, CT also revealed a large 13cm ipsilateral renal mass, concerning for renal cell carcinoma (RCC). At ureteroscopy for management of the obstructing calculus, a small papillary lesion was noted in the bladder, and excised. Histology confirmed pTa low-grade transitional cell carcinoma. Following discussion at the Urology multidisciplinary tumour board, MRI venogram (MRV) was recommended to delineate the extension of tumour into the renal vein, and to characterise a pelvic mass seen on original CT. MRV showed enhancing material extending into the IVC, consistent with tumour thrombus. However, it also identified a concerning 6cm solid ovarian mass. The patient proceeded to open right radical nephrectomy and IVC thrombectomy, hysterectomy, bilateral salpingo-oopherectomy, and omental biopsy, with combined input from Urological, Gynaecological and Vascular surgical teams. Post-operative course was uneventful. Histology showed an 11cm pT3a G2 clear cell RCC, and 7.5cm ovarian fibroma, both fully excised. This case demonstrated the serendipity of a simple ureteric calculus precipitating a cascade of investigations, that ultimately led to complete resection of three primary neoplasms.